(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The alignment of vocational education outcomes with labor market requirements is the central challenge of modern human capital development policies. Professional standards serve as the fundamental “genetic code” of this alignment, translating abstract industry needs into concrete educational outcomes.